2016
DOI: 10.1109/access.2016.2556279
|View full text |Cite
|
Sign up to set email alerts
|

A Multiuser Detection Algorithm in the Uplink SC-FDMA System for Green Communication Network

Abstract: The SC-FDMA communication scheme is the key technique in green communications and networking for 5G for the uplink of SC-FDMA multiusersystemsdue to frequency differences introducingaccess interference. The precision of the traditional parallel and serial interference cancellation algorithms is not high, and the number of required iterations for achieving satisfactory results is large. Anew algorithm for the optimal weighted parallel interference cancellation is proposed to eliminate multiple access interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…From (28), (29), (30), and (34), it can be concluded that N T points form a regular simplex for the phases proposed in (13).…”
Section: Appendix Amentioning
confidence: 93%
See 1 more Smart Citation
“…From (28), (29), (30), and (34), it can be concluded that N T points form a regular simplex for the phases proposed in (13).…”
Section: Appendix Amentioning
confidence: 93%
“…It is worth noting that the single stream GLPSM techniques require higher order underlying modulations that, in general, have greater PAPR values [30,31]. Hence, for better evaluation of the techniques, the PAPR comparison of the models is given in Fig.…”
Section: Performance Comparisonmentioning
confidence: 99%
“…The main drawback of this algorithm is the primary user's mobility statistics are only considered, whereas the secondary users mobility statistics are not considered. Bao et al developed optimal weight parallel interference cancellation algorithm (OWPIC) for cancelling the multiple access interference in wireless networks. This algorithm is based on parallel interference cancellation, and the iterations used for cancelling the interference is very less.…”
Section: Related Workmentioning
confidence: 99%
“…Accordingly, the Third-Generation Partnership Project Long-Term Evolution (3GPP-LTE) adopted SC-FDMA for uplink data transmission. Recently, SC-FDMA was also adopted in various major applications of 4th-generation (4G) LTE advanced (LTE-A) and 5th-generation (5G) new radio networks [8,9] including heterogeneous networks [10,11], multiple input and multiple output [12][13][14], machine-type communications [15,16], and green communications [17].…”
Section: Introductionmentioning
confidence: 99%